Associate inverse subsemigroups of regular semigroups - Billhardt, Bernd (2009)
By an associate inverse subsemigroup of a regular semigroup S we mean a subsemigroup T of S containing a least associate of each x ∈ S, in relation to the natural partial order ≤S. We describe the structure of a regular semigroup with an associate inverse subsemigroup, satisfying two natural conditions. As a articular application, we obtain the structure of regular semigroups with an associate subgroup with medial identity element.